If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + -12 = 52 Reorder the terms: -12 + 8y = 52 Solving -12 + 8y = 52 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 8y = 52 + 12 Combine like terms: -12 + 12 = 0 0 + 8y = 52 + 12 8y = 52 + 12 Combine like terms: 52 + 12 = 64 8y = 64 Divide each side by '8'. y = 8 Simplifying y = 8
| 37+5=35+7 | | (f+9)=39 | | -11(-x+10)=-(-x-30) | | 5(f-32)=180 | | X-1=9x+7 | | 3x/5-2/3=4x | | 6(2x-7)=-114 | | 5+32f=180 | | 3+4k=115 | | 7sen^2+5sin(-x)cosx=2-2cos^2x | | 6y^2+7-5=0 | | 3+4k=-115 | | 83-2x=20+19x | | 4x/3=33 | | 14+3(2x-5)=22 | | 3x^2-4.4x=9.6 | | 5(2x+3)-4(2-3x)=2(2+3x) | | 7p+4=-3 | | 84=-7(-3+3r) | | 7p+4=3 | | 14-(7x/2)=x-13 | | (f-32)=180 | | (-3/8)h=9 | | (86)(0.43)=x | | 81a^8+64b^12=0 | | 3c+20=-17 | | 5x-6=14+3x | | (4-i)(-21+3i)= | | -/3p?=15 | | X/315 | | -2.4(7-9y)=-48 | | 3x-7x+7=2x-35 |